Comparison of selected methods for performance evaluation of Czech and Slovak commercial banks - Gavurova, Beata; Belas, Jaroslav; Kocisova, Kristina; Kliestik, Tomas (Journal of Business Economics and Management, 2017)
The successful development of economy is based on the efficient and stable performance of commercial banks. A broad range of methods is used to evaluate them. Each method has its own specific features and logic, which results in the existence of discrepancies in the results of their evaluation. For this reason, as well as due to the elimination of model risk, numerous methods are recommended in practice to detect multidimensional disproportions in bank performance and to create a comparator base. This led to the realization of the research aimed at assessing the performance of selected Czech and Slovak banks by applying several methods and evaluating the process and outcome differences of these methods. The data were obtained from the non-consolidated financial statements published in the annual reports of the evaluated banks. The analysis showed that all methods have roughly the same results. Almost perfect correlation had been found not only among the methods of multi-criteria evaluation, but also among the other investigators.